New records, notes and new synonymies in American Cerambycidae (Coleoptera) - Heffern, Daniel; Santos-Silva, Antonio (Zootaxa, 2020)
New country records are provided for Caperonotus superbus (Aurivillius, 1897), Heterachthes picturatus Martins, 1970, Neocompsa macrotricha Martins, 1970, Neocompsa spinosa Martins, 1970, Helvina strandi (Breuning, 1942), Bebelis furcula (Bates, 1880), and Bebelis longipennis (Bates, 1885). New state records are provided for Amphicnaeia lineolata Galileo & Martins, 2011, and Dorcasta parkeri Bezark, Santos-Silva & Nascimento, 2018. The geographical distribution of Equescollum birai Nascimento, Botero & Lezama, 2019 is discussed. Chromatic variation in Heterachthes picturatus is discussed. Dorcasta gracilis Fisher, 1932 is synonymized with Dorcasta dasycera Erichson, 1849, and a new country record for the species is reported. Falsestoloides Breuning, 1954 is synonymized with Parestola Bates, 1880, Falsestoloides mexicana Breuning, 1954 is synonymized with Parestola zapotensis Bates, 1880, and a new state record is provided for the species.